Dermatological complications resulting from Immune Checkpoint Inhibitors: a case for primary care physicians - Grabowska, Hanna; Chmiel, Paulina (Family Medicine & Primary Care Review, 2025)
Immune checkpoint inhibitors (ICIs) have transformed the landscape of oncological treatment in recent years. Current estimates suggest that approximately 40% of cancer patients are eligible for ICI-based treatment across a range of clinical contexts. The mechanism of action of these agents is predicated on the stimulation of the immune system, thereby inducing the spontaneous elimination of cancer cells from the body. However, these medications also possess a distinctive toxicity profile, characterized by systemic inflammation, which can impact nearly all organs, with effects manifesting over a wide time span, ranging from the onset of therapy to long after treatment cessation. A distinctive feature of ICIs is their unique toxicity profile, characterized by the potential for systemic inflammatory responses that may affect virtually any organ. With the growing efficacy of systemic therapy, a marked improvement in cancer patient survival has been observed, including among those who achieve durable responses to treatment. Within contemporary healthcare systems, primary care physicians (PCPs) frequently constitute the initial point of contact for such patients and play a crucial role in coordinating long-term care. Cutaneous adverse events (AEs) of ICIs are the most frequently reported complications in relevant literature. Due to their often insidious, prolonged development, similarity to numerous dermatological diseases, and the risk of developing life-threatening complications, PCPs must be aware of clinical guidelines in such situations. In this review, we present a comprehensive discussion of cutaneous AEs of ICIs, diagnostic and therapeutic algorithms, and the role of primary care physicians in these processes.